Case 3676: Tupinambis indicus Daudin, 1802 (currently Varanus indicus; Reptilia, Squamata): proposed conservation of usage of the specific name by replacement of the neotype - Weijola, Valter (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Article 75.6 of the Code, is to designate a new neotype for the mangrove monitor Varanus indicus (Daudin, 1802), which is endemic to the Moluccan islands of Indonesia. The recent choice of an unrepresentative specimen to serve as neotype for this nominal species has resulted in a shift of the specific name to a different species of Varanus, V. chlorostigma (Gray, 1831) from New Guinea and surrounding islands, and the recognition of an unnecessary taxon, V. cerambonensis Philipp, Bohme & Zeigler, 1999, on Ambon, Seram and Buru in the Moluccas. To conserve the name indicus in its original usage and to avoid further taxonomic confusion, it is proposed that the current neotype specimen be replaced by a new one that belongs to the original taxonomic species involved, thereby reducing V. cerambonensis to a junior subjective synonym of V. indicus and also conserving V. chlorostigma in its accustomed use as the valid name for the New Guinean species.
Keywords: Nomenclature; taxonomy; Varanidae; Varanus chlorostigma; neotype; southwestern Pacific; Moluccas; Ambon; Ravak; New Guinea